Efektivitas Ruang Terbuka Hijau Mikro Sebagai Intervensi Penurunan Polusi Udara Lokal - Alya Fajria Rahma Maulida; Dwi Atmanto; Agung Purwanto; Afif Amir Amrullah (Poltekkes Kemenkes Semarang, 2025)
Increased air pollution concentrations in densely populated urban areas have an impact on public health and environmental comfort. Limited space for greening in large cities such as Jakarta has created a need for more flexible and efficient solutions. In this context, Micro Green Open Spaces (RTH Mikro) are seen as one strategy that can be applied at the neighborhood level to help reduce local air pollution. This study examines the role of Micro Green Open Spaces (RTH Mikro) in reducing air pollution in densely populated urban areas such as East Jakarta. RTH Mikro is identified as an adaptive solution to land constraints in urban areas. Using a qualitative descriptive approach, this study analyzes the effectiveness of Micro Green Open Spaces, particularly in Taman Dukuh, through field observations, vegetation identification, and estimates of emissions from mobile and stationary sources. The results show that the dominant vegetation in Taman Dukuh, such as trembesi and flamboyant trees, has significant ecological potential in filtering PM2.5, absorbing CO₂, and cooling the local temperature. Although the study area has high pollutant levels due to heavy traffic, the presence of Micro-Green Open Spaces significantly intervenes in the spread of pollutants and improves air quality. This study concludes that optimizing the function of Micro-RTH vegetation is essential for improving urban air quality, with recommendations for spatial design and sustainable maintenance. This finding supports the strategic planning of Micro Green Spaces as a key element in sustainable urban planning.